Magic and ritual in the ancient world - Mirecki, Paul Allan.; Meyer, Marvin, 1948- (Religions in the Graeco-Roman World, 2002)
This volume contains a series of provocative essays that explore expressions of magic and ritual power in the ancient world. The essays are authored by leading scholars in the fields of Egyptology, ancient Near Eastern studies, the Hebrew Bible, Judaica, classical Greek and Roman studies, early Christianity and patristics, and Coptic and Islamic Egypt. The strength of the present volume lies in the breadth of scholarly approaches represented. The book begins with several papyrological studies presenting important new texts in Greek and Coptic, continuing with essays focusing on taxonomy and definition. The concluding essays apply contemporary theories to analyses of specific test cases in a broad variety of ancient Mediterranean cultures.